Investigation of bioactive compounds from sea cucumber extract and stingless bee honey using critical literature review and bioinformatics approach for potential synergy combination - Hafiz Leong (Progress in Engineering Application and Technology, 2021)
Stingless bee and sea cucumber can both be found locally in Malaysia, with local species. One major product that has been commercialized on a large scale in Malaysia from stingless bees is the stingless bee honey, commonly known as kelulut. There is increasing research that shows the benefits of kelulut honey for human health, including its potential use in managing blood sugar levels for diabetes and obesity prevention. Meanwhile, sea cucumber has also been traditionally consumed as a food delicacy in Malaysia, and Malaysian sea cucumbers are being exported in dried form worldwide for food consumption. Besides its nutritious composition, several sea cucumber species such Stichopus horrens or commonly called ‘gamat emas’ by Malaysians are traditionally used for wound healing purposes in the forms of oil for external use, or ingested in liquid form for internal use. Published studies demonstrated that sea cucumbers have bioactive compounds that are beneficial for human health.   In this study, the feasibility of a synergy between sea cucumber extract and stingless bee honey for positive medical and health impact will be looked into using bioinformatics approaches and critical literature reviews. Enzymes and proteins identified to be of medical importance were identified and underwent physicochemical analysis, secondary and tertiary protein model prediction, and protein-ligand docking were performed. The study proposed that the combination of kelulut honey with sea cucumber extract will show a positive synergy and have greater activity than on their own. It is hoped that this study could be a starting point to investigate the potential of combining kelulut honey with sea cucumber extract as a novel functional supplement.